Mutational analysis identifies functional domains in the influenza A virus PB2 polymerase subunit. - Perales, B (1996)
A collection of influenza virus PB2 mutant genes was prepared, including N-terminal deletions, C-terminal deletions, and single-amino-acid insertions. These mutant genes, driven by a T7 promoter, were expressed by transfection into COS-1 cells infected with a vaccinia virus encoding T7 RNA polymerase. Mutant proteins accumulated to levels similar to that of wild-type PB2. Immunofluorescence analyses showed that the C-terminal region of the protein is essential for nuclear transport and that internal sequences affect nuclear localization, confirming previous results (J. Mukaijawa and D. P. Nayak, J. Virol. 65:245-253, 1991). The biological activity of these mutants was tested by determining their capacity to (i) reconstitute RNA polymerase activity in vivo by cotransfection with proteins NP, PB1, and PA and a virion-like RNA encoding the cat gene into vaccinia virus T7-infected COS-1 cells and (ii) complete with the wild-type PB2 activity. In addition, when tested at different temperatures in vivo, two mutant PB2 proteins showed a temperature-sensitive phenotype. The lack of interference shown by some N-terminal deletion mutants and the complete interference obtained with a C-terminal deletion mutant encoding only 124 amino acids indicated that this protein domain is responsible for interaction with another component of the polymerase, probably PB1. To further characterize the mutants, their ability to induce in vitro synthesis of viral cRNA or mRNA was tested by using ApG or beta-globin mRNA as a primer. One of the mutants, 1299, containing an isoleucine insertion at position 299, was able to induce cRNA and mRNA synthesis in ApG-primed reactions but required a higher beta-globin mRNA concentration than wild-type PB2 for detection of in vitro synthesis. This result suggested that mutant I299 has diminished cap-binding activity.